Предмет: Алгебра,
автор: Аноним
Знайдіть значення виразу (2-х)(2+х)(х-1)+х²(х-1) при х=1,8.
Допоможіть будь-ласка!
Ответы
Автор ответа:
0
2^2-х^2(х-1)+х^2(х-1)=4-х^2(х-1)+х^2(х-1)=4-(х-1)+х^2(х-1)=В жоп# всё
Автор ответа:
0
(2-х)(2+х)(х-1)+х²(х-1)=(4-х²)(х-1)+х²(х-1)=(х-1)(4-х²+х²)=(х-1)*4
(1,8-1)*4=0,8*4=3,2
Автор ответа:
0
Допоможіть будь-ласка! http://znanija.com/task/4873640
Похожие вопросы
Предмет: Математика,
автор: tarnovskiy207
Предмет: История,
автор: resetnikova291
Предмет: Другие предметы,
автор: Аноним
Предмет: Алгебра,
автор: misszboom
Предмет: Литература,
автор: Настя766